2000
DOI: 10.1097/00004872-200018080-00018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brain natriuretic peptide as marker of left ventricular dysfunction and hypertrophy in the population

Abstract: The current study provides new insight into regulation and diagnostic value of BNP in middle-aged subjects and demonstrates important independent effects of LV function and mass upon BNP plasma concentrations. Although measurement of BNP cannot be recommended for the detection of marginally impaired LV function in the population, it may be helpful to suggest or exclude severe LV dysfunction with concomitant hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
78
1
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 25 publications
9
78
1
10
Order By: Relevance
“…In this study with 32 patients, we found NT-proBNP to be a reliable marker to make this differentiation with a sensitivity of 100% and a specificity of 83%. This is comparable to the literature for diagnosis of cardiac dysfunction in the general population (McDonagh et al, 1998;Luchner et al, 2000) or in patients suspected to have heart failure (Cowie et al, 1997;Maisel et al, 2002Maisel et al, , 2003. The PPV of 69% as described in our study is relatively high compared to studies in the general population with a PPV of approximately 30% (Bay et al, Figure 3 The ROC curve shows that the accuracy to differentiate between patients with and without heart disease is the best in NT-proBNP compared to ANP levels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this study with 32 patients, we found NT-proBNP to be a reliable marker to make this differentiation with a sensitivity of 100% and a specificity of 83%. This is comparable to the literature for diagnosis of cardiac dysfunction in the general population (McDonagh et al, 1998;Luchner et al, 2000) or in patients suspected to have heart failure (Cowie et al, 1997;Maisel et al, 2002Maisel et al, , 2003. The PPV of 69% as described in our study is relatively high compared to studies in the general population with a PPV of approximately 30% (Bay et al, Figure 3 The ROC curve shows that the accuracy to differentiate between patients with and without heart disease is the best in NT-proBNP compared to ANP levels.…”
Section: Discussionsupporting
confidence: 86%
“…Large studies in the general population or in noncardiac patients showed that measuring natriuretic peptides might be an effective screening method for left-ventricular systolic dysfunction (McDonagh et al, 1998;Luchner et al, 2000;Bay et al, 2003). In patients with the suspicion of heart failure several other studies showed natriuretic peptides to be useful indicators for the detection of heart failure (Lerman et al, 1993;Davidson et al, 1996;Cowie et al, 1997;Hammerer-Lercher et al, 2001;Maisel et al, 2002Maisel et al, , 2003.…”
mentioning
confidence: 99%
“…This finding is supported by population-based studies, where subjects with LVH or left ventricular systolic dysfunction have been shown to have increased levels of NP, but NP have not been reported to correlate with BP or LVM. 8,9,24 Furthermore, plasma BNP levels are not increased in cyclists with significant LVH, 25 and we have shown that most of the patients with non-obstructive hypertrophic cardiomyopathy attributable to the Asp175Asn mutation in the a-tropomyosin gene and marked LVH have normal plasma NT-proBNP levels. 26 Although LA size is an independent predictor of cardiovascular mortality and morbidity, 27,28 the mechanism of the LA enlargement remains poorly elucidated.…”
Section: Discussionmentioning
confidence: 68%
“…5 Elevated levels of natriuretic peptides (NPs) in hypertension often have been attributed to the presence of LVH. 6,7 Although NP are not useful for community screening for LVH, 8,9 they might be useful for the early detection of LVH in patients with essential hypertension. 7 Although the association between NP and LVH has been demonstrated in patients with severe hypertension and high prevalence of LVH, 6,7 the applicability of this data to patients with mild hypertension is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pro-BNP have received major attention as cardiovascular marker because this peptide is secreted in case of volume overload and increased ventricular wall tension (19)(20)(21). In addition, pro-BNP was identified as a discerning marker of LVH and/or early LVD.…”
Section: Discussionmentioning
confidence: 99%